3,8-Dimethyl-4-oxo-3,4-dihydroquinazoline-6-carbonitrile - Hai-Yan Tian; Jian-Cong Bi; Hong-Xia Zhang; Juan Zhang (Acta Crystallographica Section E, 2012)
In the title compound, C11H9N3O, the quinazoline unit is almost planar, with a mean deviation of 0.006 (1) Å from the least-squares plane defined by the ten constituent atoms. In the crystal, molecules are linked by weak C—H...N hydrogen bonds.